Thermal Characteristics of Oil Film in Critical Lubrication State of Heavy Hydrostatic Bearing - Yanqin, Zhang; Ye, Wu; Jiabao, Li; Mulan, Wang; Zhen, Quan (Recent Patents on Mechanical Engineering, 2024)
Background: Lubrication failure has always been a concern in the research of heavy hydrostatic bearings. A preliminary study found that under a certain working condition, the heavy hydrostatic bearing will appear in the condition of zero local flow of oil film, which is called a critical lubrication state. It produces a significant thermal accumulation effect and affects the lubrication performance of the bearing. Objective: This paper takes Q1-205 double rectangular cavity hydrostatic thrust bearing as the research object and adopts the research method combining theoretical analysis, simulation, and experimental test to analyze the temperature rise and characteristics of the bearing when it is in critical lubrication state under different working conditions. Methods: The finite volume method is used to simulate the critical lubrication state under the condition of common load and rotating speed, and the corresponding operating parameters of the critical lubrication of heavy static support are obtained. Results: It is found that when the oil film is in the critical lubrication state, the low temperature zone is concentrated at the bearing position of the oil film, while the high temperature zone is concentrated at the counter-current side sealing edge. Conclusion: The oil film's local temperature rise is intensified, and the heat accumulation phenomenon is serious because the heat cannot be taken away in time.
Keywords: temperature rise